Технология и техника добычи нефти и газа: учебное пособие для втузов - Муравьев И. М. Иван Михайлович; Базлов М. Н. Михаил Николаевич; Жуков А. И. Анатолий Иванович; Чернов Б. С. Бронислав Семенович (Москва, Недра, 1971)
Загл. указано на пер.